Youth Transitions, International Student Mobility and Spatial Reflexivity Being Mobile? - Cairns, D.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Drawing on comparative country case studies, this book explores student mobility in Europe, incorporating original theoretical perspectives to explain how mobility happens and new empirical evidence to illustrate how students become mobile within their present educational and future working lives.
Keywords: Human geography; Educational sociology .; Education and sociology; Educational sociology; Education; Youth—Social life and customs; Higher education; Human Geography; Sociology of Education; Sociology of Education; Education, general; Youth Culture; Higher Education